Integrasi Agama dan Sains dalam Perspektif M. Naquib Al-Attas - Larasati, Septri; M, Amril; Dewi, Eva (TABYIN: JURNAL PENDIDIKAN ISLAM, 2024)
This research describes the integration of religion and science from the perspective of M. Naquib Al-Attas. The aim of this research is to understand the biography of M. Naquib al-Attas, al-Attas's religious and scientific thinking, al-Attas' methodology for integrating religion and science and the Islamization of al-Attas' knowledge. The study method used is literature study or library research by collecting various information from journals/literature related to the Integration of Religion and Science in the Perspective of M. Naquib Al-Attas. Data collection with the results of previous research which support the data in this research. The result is that Al-Attas stated that there is an incompatibility between modern western science and technology and the Islamic system of epistemology and metaphysics. This is because science does not involve the role of God the Khaliq who has created natural laws, so science tends to conflict with religion. Since the 1970s Al-Attas began to introduce the concept of Islamization of science. Islamization as echoed by al-Attas is a term that brings something into Islam or makes it and makes it Islamic in accordance with the spirit of Islamic epistemology as a step or an effort to understand everything within an Islamic framework.